Corona Virus Disease 2019 - Diah Handayani; Dwi Rendra Hadi; Fathiyah Isbaniah; Erlina Burhan; Heidy Agustin (Jurnal Respirologi Indonesia, 2020)
Corona virus disease 2019 (COVID-19) is a new name given by World Health Organization (WHO) of 2019 novel corona virus infection, reported at the end of 2019 from Wuhan, Cina. The spread of infection occurs rapidly and creates a new pandemic threat. Etiology of COVID-19 was identified in 10 January 2020, a betacorona virus, similar with severe acute respiratory syndrome (SARS) and middle east respiratory syndrome (MERS CoV). The clue diagnosis pathway of COVID-19 were history of travel from Wuhan or others infected countries within 14 days prior, and symptoms of acute respiratory illness (ARI) or lower respiratory infection (pneumonia) with the result of real time polymerase chain reaction (RT-PCR) specific for COVID-19. The WHO classified COVID-19 into suspect case, probable case and confirmed case. Indonesia Ministry of Health classified the case into in monitoring (ODP), patient under surveillance (PDP), people without symptom (OTG) and confirmed case. Specimens for detection COVID-19 could be acquired from nasal and nasopharynx swab, sputum and another lower respiratory aspirate including broncoalveolar lavage (BAL). Management of COVID-19 consist of isolation and infection control, supportive treatment according to the disease severity which could be mild (acute respiratory infection) to severe pneumonia or acute respiratory distress syndrome (ARDS). Disease transmission is via droplets and contact with droplets. Currently, there is no antiviral and vaccine. Prevention is very important for this disease by limitation of transmission, identification and isolate patients. Prognosis is determined by severity of the disease and patient comorbidity. Information about this novel disease remains very few, studies are still ongoing and is needing further research to fight with this new virus. (J Respir Indo. 2020; 40(2): 120-30)